Anti-SARS-CoV-2 Antibodies Within IVIg Preparations: Cross-Reactivities With Seasonal Coronaviruses, Natural Autoimmunity, and Therapeutic Implications - Dalakas, Marinos C.; Bitzogli, Kleopatra; Alexopoulos, Harry (Frontiers in Immunology, 2021)
Abstract Introduction: Cross-reactivity to SARS-CoV-2 antigenic peptides has been detected on T-cells from pre-pandemic donors due to recognition of conserved protein fragments within members of the coronavirus’s family. Further, preexisting antibodies recognizing SARS-CoV-2 with conserved epitopes in the spike region have been now seen in uninfected individuals. High-dose Intravenous Immunoglobulin (IVIg), derived from thousands of healthy donors, contains natural IgG antibodies against various antigens which can be detected both within the IVIg preparations and in the serum of IVIg-receiving patients. Whether IVIg preparations also contain antibodies against pre-pandemic coronaviruses or autoreactive antibodies that cross-react with SARS-CoV-2 antigenic epitopes, is unknown. Methods: 13 samples from 5 commercial IVIg preparations from pre-pandemic donors (HyQvia (Baxalta Innovations GmbH); Privigen (CSL Behring); Intratect (Biotest AG); IgVena (Kedrion S.p.A); and Flebogamma (Grifols S.A.) were blindly screened using a semi-quantitative FDA-approved and validated enzyme-linked immunosorbent assay (ELISA) (Euroimmun, Lubeck, Germany). Results: Nine of thirteen preparations (69.2%) were antibody positive based on the manufacturer's cut-off (index of sample OD to calibrator OD > 1.1). From those, 7/9 (77%) had titers as seen in asymptomatically infected individuals or recent COVID19-recovered patients, while 2/9 (23%) had had higher titers, comparable to those seen in patients with active symptomatic COVID-19 infection (index > 2.2 ). Conclusion: Pre-pandemic IVIg donors have natural autoantibodies against antigenic protein fragments conserved among the “common cold”- related coronaviruses. The findings are important in a) assessing true anti-SARS-CoV-2-IgG seroprevalence avoiding false positivity in IVIg-receiving patients; b) exploring potential protective benefits in patients with immune-mediated conditions and immunodeficiencies receiving acute or chronic maintenance therapy and c) validating data from a recent controlled study that showed significantly lower in-hospital mortality in the IVIg- treated group